JAPANESE MODEL OF CORPORATE GOVERNANCE BY ENTERPRISE STRUCTURES (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The essence of the Japanese model of corporate management of entrepreneurial structures is considered. Identified signs of corporate governance in Japan. It is noted that the corporate governance philosophy of Japan is based on the main tenet of Toyota, to bring benefits to society by producing high quality products and services. The practice of doing business on this principle has formed the values, beliefs and methods of work that have allowed to achieve competitive advantages. The combination of these methods of work and values is the philosophy of Toyota management. The activities of corporations are based on the observance of 14 principles of management.The combination of these methods of work and values is the philosophy of Toyota management, which is realized in 14 principles: 1. To make management decisions in the long-term perspective, even if it affects short-term financial goals. 2. The process as a continuous flow reveals problems. 3. Use of the deferral system to avoid overproduction. 4. Distribution of volumes of work evenly (heyzunka): it is necessary to work as a tortoise, and not as a hare. 5. Production must be stopped in order to solve problems through production culture, if required by quality. 6. Standard tasks are the basis for continuous improvement and delegation of authority to employees. 7. Use visual inspection in such a way that no problem remains unnoticed. 8. Only a reliable, proven technology should be used. 9. Education leaders who are perfectly aware of their business, profess the philosophy of the corporation and can teach this to others. 10. It isnecessary to educate people and form teams that profess the philosophy of the company. 11. It is necessary to respect their partners and suppliers, to put difficult tasks ahead of them and to help them to improve. 12. To understand the situation, one has to see everything with his own eyes (Gent Gentbuzz). 13. It is necessary to take decisions without hesitation, by consensus, weighing all possible options; Immediately introducing it (nemvasi). 14. Becoming a structure that can be trained through unceasing self-examination (khansay) and continuous improvement (kaizen). It is they who ensure successful and productive activity of Japanese enterprises, which forms a positive image not only of corporations, but also of countries on world markets.
Keywords: model, corporation, entrepreneurial structures, corporate governance, philosophy, Toyota